Optimum Design of Transmission Efficiency of Torus Envelope Arc Cylindrical Worm Pair - Qu Dongyue; Zhang Chunyu; Xu Jian’an; Zhang Rilai (Jixie chuandong)
Based on the gear meshing principle and the meshing theoretical mathematical model of torus enveloping circular arc worm pair（ ZC1）,the changing trend of momentary contact line of worm pair is obtained. The influence of its basic parameters on the induced curvature,lubrication angle and instantaneous contact line and the speed of the direction of the angle between the impact are analyzed. Choosing the three parameters of modulus m,displacement coefficient x and lead angle γ,which have a greater impact on the transmission quality as a design variable to establish optimization model. By using the particle swarm optimization,the efficiency of circular torus envelope arc cylindrical worm gear is optimized. By using the KISSsoft and comparing the results before and after optimization,the simulation result shows that the optimized efficiency of torus worm gear pair with torus envelope envelopment is improved to a certain extent,which is of great significance to the parameter design of torus enveloping circular worm pairs.